2018
DOI: 10.1080/20018525.2018.1552064
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic yield and safety of EUS-FNA biopsy in sub-aortic and para-aortic lymph node stations with the trans-aortic approach: a case series and literature review

Abstract: Background: Sub-aortic (station 5) and para-aortic (station 6) lymph nodes are not easily accessible due to the interposition of the aorta and the left pulmonary artery. Taking a biopsy from those stations could be of value when there are no other mediastinal lymph node stations or when biopsy in other sites failed to reach a diagnosis. Surgery is the gold standard technique in the evaluation of those stations; endoscopic ultrasound-fine needle aspiration (EUS-FNA) has been proposed as a minimally invasive tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 20 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…23 Hence, during transarterial puncture, areas of significant atherosclerosis should be avoided. 14,19 Study by Naaman et al reported a total of four major adverse events in their series of 35 patients who underwent EBUS-guided TVNA, of which two were self-limited episodes of hemoptysis, one with acute exacerbation of COPD requiring ICU stay and one developed atrial fibrillation which was reversed with anti-arrythmics. 25 Von 24 This shows that E-TVNA can be performed with minimal adverse events, with spontaneous resolution of adverse events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Hence, during transarterial puncture, areas of significant atherosclerosis should be avoided. 14,19 Study by Naaman et al reported a total of four major adverse events in their series of 35 patients who underwent EBUS-guided TVNA, of which two were self-limited episodes of hemoptysis, one with acute exacerbation of COPD requiring ICU stay and one developed atrial fibrillation which was reversed with anti-arrythmics. 25 Von 24 This shows that E-TVNA can be performed with minimal adverse events, with spontaneous resolution of adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…The search strategy yielded 173 records of which 114 were screened after removal of duplicate records. After assessing for eligibility, a total of 17 studies [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] with 411 patients were included in the final analysis.…”
Section: Study Characteristics and Quality Analysismentioning
confidence: 99%
“…Since Vincent et al and Wallace et al (2006 and 2007, respectively) published papers on the first transvascular (pulmonary artery and aorta) puncture guided by EBUS and EUS, respectively, only a few case reports and small case series have been published 7 8 . Much of the current literature on EUS-TV-FNA has paid special attention to intrathoracic lesions, and most of the knowledge about this technique comes from the EBUS field 9 10 11 12 . Many of the reports related to EUS-guided FNA involve the transaortic approach and focus on the study of lung cancer 4 8 13 14 15 .…”
Section: Discussionmentioning
confidence: 99%
“…An updated literature review is included ( Table 5 ), and three retrospective case series stand out for comparison to our results 4 8 9 11 12 13 14 15 16 20 21 .…”
Section: Discussionmentioning
confidence: 99%
“…As transvascular access with a small gauge needle is now routinely being used in radiological and interventional vascular procedures, recent studies have reported the use of transvascular EBUS-TBNA [7] and EUS-FNA [8]. Subsequently, the feasibility and safety of these procedures have been evaluated in a series of clinical studies [9][10][11][12][13][14][15][16][17][18]. Furthermore, the important precautions and technical aspects of EBUS-TBNA and EUS-FNA have been discussed [19].…”
Section: Introductionmentioning
confidence: 99%